Vegetative development and content of calcium, potassium, and sodium in watermelon under salinity stress on organic substrates - Silva Júnior, Eugênio Gonçalves da; Silva, Anselmo Ferreira da; Lima, Jucelino de Sousa; Silva, Maria de Fátima Caetano da; Maia, Josemir Moura (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the vegetative development and determine the concentration of sodium, potassium, and calcium in watermelon (Citrullus lanatus) grown on two organic substrates and under increasing saline concentrations. The substrates were soil + earthworm humus (S1) and soil + bovine manure (S2), and the saline treatments consisted of irrigation water with different electrical conductivities: 1.36 (control), 3.56, 5.76, and 7.96 dS m-1. The experimental design used was a randomized complete block in a 2×4 (substrate × conductivity) factorial arrangement with five replicates. Main branch length, root length, stem diameter, leaf number, leaf area, and fresh matter mass of shoots and roots, as well as the sodium, potassium, and calcium contents in the plants, were determined. All phenological parameters interacted with the substrates, and S1 improved plant performance. Substrates interacted significantly with: leaf area; leaf number; stem diameter; main branch length; root length; fresh matter mass of shoots and roots; and the contents of sodium, potassium, and calcium, in both shoots and roots of watermelon irrigated with saline water for up to 27 days after emergence. There are also interactions between substrates and salinity for stem diameter, main branch length, fresh matter mass of roots, and calcium contents in both shoots and roots, and potassium and sodium contents in the roots.